Net neutrality in a "peripheral" but pioneering country : policy processes, consequences, and developments in Slovenia - Milosavljević, Marko, medijski stručnjak (Array, 2019)
This paper analyses policies and regulation addressing net neutrality in Slovenia. It traces them from their bold beginnings in 2012 to their harmonisation with prevailing trends and practices in the European Union, following the enactment of EU rules on net neutrality in 2016. The study, based on qualitative document analysis and supplemented by interviews with stakeholders, showed that Slovenia was not successful in advocating stronger EU net neutrality safeguards. The rules of the single digital market within the EU with the limited subsidiarity of member states made it impossible to apply the original Slovenian legal safeguards. This indicates a reduced potential of nation states to advocate their communication policy objectives within the EU framework on one hand, and their ability to infl uence EU policymaking by encouraging a quicker common response with independent action on the other. Further research is required into the potential re-evaluation and extension of the concept of net neutrality, to address the full extent of discriminatory treatment of internet traffic, not limited solely to networks.